2023
DOI: 10.3390/ph16050755
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances Cytotoxic Effects of Cisplatin by Inducing Cell Cycle Arrest and Apoptosis in Ovarian Adenocarcinoma SKOV-3 Cells through Activating the p38 MAPK and Suppressing AKT

Abstract: In the current study, we identified a mechanism of resveratrol (RES) underlying its anti-cancer properties against human ovarian adenocarcinoma SKOV-3 cells. We investigated its anti-proliferative and apoptosis-inducing effects in combination with cisplatin, using cell viability assay, flow cytometry, immunofluorescence study and Western blot analysis. We discovered that RES suppressed cancer cell proliferation and stimulated apoptosis, especially when combined with cisplatin. This compound also inhibited SKOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In addition, the resveratrol group had higher Bcl-2 expression and lower Bax, caspase-3, and cytochrome c expression than the model group. Recently accumulated evidence confirm that Resveratrol stimulate P38-MAPK and suppress AKT activation in ovarian cancer cells may be via activation of signaling molecules suh as ERK1/2 and JNK these effect of resveratrol enhanced cisplatin inducing cell cycle arrest by downregulation the expression of responsible cycle proteins and activation caspase and has been an observed rise which occur in apoptotic cells [48]. RES alters the metabolic reprogramming of Staphylococcal enterotoxin-B (SEB) -activated immune cells, through suppression of mTOR activation and its downand upstream effects on energy metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the resveratrol group had higher Bcl-2 expression and lower Bax, caspase-3, and cytochrome c expression than the model group. Recently accumulated evidence confirm that Resveratrol stimulate P38-MAPK and suppress AKT activation in ovarian cancer cells may be via activation of signaling molecules suh as ERK1/2 and JNK these effect of resveratrol enhanced cisplatin inducing cell cycle arrest by downregulation the expression of responsible cycle proteins and activation caspase and has been an observed rise which occur in apoptotic cells [48]. RES alters the metabolic reprogramming of Staphylococcal enterotoxin-B (SEB) -activated immune cells, through suppression of mTOR activation and its downand upstream effects on energy metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…The inhibition of PI3K/Akt/mTOR pathway in vitro showed the effect on decreased chemoresistance of epithelial OC cells by the use of dactolisib in combination with cisplatin, increasing both ROS production and apoptosis mechanisms, and thus decreasing rates and outcomes of EMT [ 140 ]. Likewise, patient-derived OC spheroids cultured in vitro with LY-294002—a PI3K-Akt dual kinase inhibitor—showed a significant decrease in cancer stemness and chemoresistance to cisplatin [ 141 ], and resveratrol-treated OC cells SKOV-3 displayed increased apoptosis and induced cell cycle arrest through Akt suppression in vitro [ 142 ].…”
Section: Pi3k/akt Pathway In Ovarian Cancermentioning
confidence: 99%
“…However, most patients develop inherent or acquired drug resistance to CDDP ( Rocha et al, 2018 ). RES treatment significantly enhances the sensitivity of SKOV-3 cells to CDDP ( Hankittichai et al, 2023 ). Specifically, the combination of RES and CDDP activates caspase-3, caspase-9, and poly (ADP-ribose) polymerase (PARP); inhibits cyclin A2 and cyclin B1 expression; and induces cell cycle arrest in the S phase, ultimately inhibiting cell proliferation and promoting apoptosis.…”
Section: Combined With Antitumor Drugs Res Increases Efficacy and Red...mentioning
confidence: 99%
“…Specifically, the combination of RES and CDDP activates caspase-3, caspase-9, and poly (ADP-ribose) polymerase (PARP); inhibits cyclin A2 and cyclin B1 expression; and induces cell cycle arrest in the S phase, ultimately inhibiting cell proliferation and promoting apoptosis. Further experiments revealed that RES strongly activates p38 phosphorylation and inhibits AKT activation ( Hankittichai et al, 2023 ). Yue et al (2019) showed that RES enhances the sensitivity of HeLa cells to CDDP by inducing G1 phase blockage and apoptosis.…”
Section: Combined With Antitumor Drugs Res Increases Efficacy and Red...mentioning
confidence: 99%